EDUARD SCHWARTZ AND THE ACTA CONCILIORUM OECUMENICORUM - Turner, C. H. (The journal of theological studies, 1929)
C. H. TURNER; EDUARD SCHWARTZ AND THE ACTA CONCILIORUM OECUMENICORUM, The Journal of Theological Studies, Volume os-XXX, Issue January, 1 January 1929, Pages 11